Feminist Analysis of Beauty Privilege and Marginalization in Wicked (2024) - Noviana Mega Saputri; Yusrina Dinar Prihatika (Journal of English Language and Education, 2026)
This paper explores how the film Wicked (2024) constructs beauty privilege by contrasting the representations of Glinda and Elphaba, focusing on the interplay between physical appearance and power relations. Through a qualitative analysis of representation, the study investigates both visual and textual components in pivotal scenes, drawing on Stuart Hall’s theory of representation alongside Naomi Wolf’s feminist perspectives. The results indicate that Glinda’s alignment with conventional American beauty ideals affords her social acceptance and narrative dominance, whereas Elphaba’s unconventional looks lead to her marginalization despite her eventual defiance. Wicked (2024) both upholds and critiques established beauty hierarchies, illustrating how beauty functions as a political tool that influences identity formation, power structures, and social legitimacy within contemporary Hollywood cinema. Few studies explore how beauty advantage creates "othering," especially in molding Elphaba's marginalization in Wicked (2024), despite earlier research on beauty standards in movies.